1987
DOI: 10.1007/bf00284100
|View full text |Cite
|
Sign up to set email alerts
|

Further evidence for genetic heterogeneity in the fragile X syndrome

Abstract: The X-linked fragile X [fra(X)] syndrome, associated with a fragile site at Xq27.3, is the most common Mendelian inherited form of mental deficiency. Approximately 1 in 1060 males and 1 in 677 females carry the fra(X) chromosome. However, diagnosis of carrier status can be difficult since about 20% of males and 44% of females are nonpenetrant for mental impairment and/or expression of fra(X). We analyzed DNA from 327 individuals in 23 families segregating fra(X) for linkage to three flanking polymorphic probes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

1987
1987
1992
1992

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…It is well established that apparently unaffected males are able to transmit the fra(X) gene to their daughters [Martin and Bell, 1943;Webb et al, 1981;Fryns and Van den Berghe, 1982;Gardner et al, 1983;Froster-Iskenius et al, 1984;Pembrey et a1.,1984;Brown et al, 1985;1987;HowardPeebles and Friedman, 1985;Loesch et al, 1987;Holmgren et al, 19881. Most of these reports do not mention affected brothers and sisters of such NTM's.…”
Section: Discussionmentioning
confidence: 98%
“…It is well established that apparently unaffected males are able to transmit the fra(X) gene to their daughters [Martin and Bell, 1943;Webb et al, 1981;Fryns and Van den Berghe, 1982;Gardner et al, 1983;Froster-Iskenius et al, 1984;Pembrey et a1.,1984;Brown et al, 1985;1987;HowardPeebles and Friedman, 1985;Loesch et al, 1987;Holmgren et al, 19881. Most of these reports do not mention affected brothers and sisters of such NTM's.…”
Section: Discussionmentioning
confidence: 98%
“…Mattei, Centre de Genetique Medicale, HBpital d'Enfants de la Timone, 13385 Marseille Cedex 5, France. o 1991 Wiley-Liss, Inc. still unclear. Genetic heterogeneity has been suggested in several reports [Brown et al, 1985[Brown et al, ,1987Giannelli et al, 19871 and analysis of a large body of data has shown that the affection is transmitted through phenotypically normal males, termed transmitting males [Sherman et al, 1984[Sherman et al, ,1985Loeschet al, 19871. Genetic counseling in the fra(X) syndrome requires a complete family analysis including the clinically normal males.…”
Section: Introductionmentioning
confidence: 95%
“…Several studies have found tight linkage (0 = 0.05; Drayna and White, 1985;Brown WT et al 1987a;Arveiler et al 1988) whereas one large family shows loose linkage Veenema et al 1987; 8 recombinants in 32 meioses).…”
Section: Family Studiesmentioning
confidence: 99%